A review on Somaclonal variation of Theobroma cacao / Ahmad Muzzammil Bakri and Asmah Awal - Bakri, Ahmad Muzzammil; Awal, Asmah (Faculty of Plantation and Agrotechnology, 2018)
Theobroma cacao is mainly grown in the tropical regions of the world at rain forest areas and domestically cultivated for its beans production. Tissue culture is one of the important tools for plant breeding and research. The presence of somaclonal variation derived from tissue culture could cause changes in the plant. The change in agronomic traits is the sources to new clones/variants either the traits is positive or negative. In developing somaclonal variation of Theobroma cacao each of the tissue culture method has different result. Besides, the problem of somaclonal variation is not only caused by one factor and somaclonal variation is random and unpredictable phenomena. Besides, there is a problem in determine the best method in detecting, somaclonal variations in cocoa. These reviews provide an overview of the possible factors of somaclonal variation that may cause by pre-existing variation or tissue culture induced variation. Pre-existing variation factor listed are chimeras, chromosomes aberration and rearrangement, cell cycle and transposable element. Induced variation reviewed are propagation method, explants source, type and concentration of Plant Growth Regulator (PGR), number and duration of subculture, effect of stress and genotype and ploidy level. These papers also review about effect of somaclonal variation either positive, negative or positive-negative effect. Besides, technique to overcome somaclonal variation using morphological detection, physiological/biochemical detection and molecular detection also reviewed. Benefits, negative aspect and risks of somaclonal variation toward human, environment and economy either directly or indirectly by taking consideration of public acceptance also discussed in this paper. Additionally, cocoa tissue culture technique from the past and present such as nucellar somatic embryo, zygotic embryo, somatic embryogenesis, somatic embryo-derived plant (SEP), and temporary immersion system (TIS) also summarized in this review.